2011
DOI: 10.1021/jo2016696
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Catalyzed Direct Three-Component Aza-Diels–Alder Reaction Using Hen Egg White Lysozyme

Abstract: The direct three-component aza-Diels-Alder reaction of aromatic aldehyde, aromatic amine, and 2-cyclohexen-1-one was catalyzed by hen egg white lysozyme for the first time. Under the optimized conditions investigated in this paper, the enzyme-catalyzed aza-Diels-Alder reaction gave yields up to 98% and stereoselectivity of endo/exo ratios up to 90:10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 23 publications
(14 reference statements)
0
20
0
1
Order By: Relevance
“…The transformation has broad scope and tolerates different amines and aldehydes. [78] The stereoselectivity of the reaction can be modulated by variation of temperature and solvent. For instance, complete diastereoselectivity in favor of the exo-product 140 was observed if the reaction was carried out at 25 8C in pure water.…”
Section: Methodsmentioning
confidence: 99%
“…The transformation has broad scope and tolerates different amines and aldehydes. [78] The stereoselectivity of the reaction can be modulated by variation of temperature and solvent. For instance, complete diastereoselectivity in favor of the exo-product 140 was observed if the reaction was carried out at 25 8C in pure water.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the direct three‐component aza‐Diels–Alder reaction between an aromatic aldehyde (1 equiv), aromatic amine (3 equiv) and 2‐cyclohexen‐1‐one (3 equiv) was catalyzed by hen egg‐white lysozyme (HEWL), a hydrolase from the glycosylase family. The azabicycles were obtained in 69–97% isolated yields and an endo / exo selectivity up to 90:10 after several days in a mixture of MeCN/water (9:1) at 35°C (Scheme ) . Furthermore, 4‐thiazolidinones have been efficiently obtained in a one‐pot reaction between an amine, an aldehyde, and mercaptoacetic acid used in equimolar amounts, catalyzed by trypsin from porcine pancreas (42–89% isolated yield, Scheme ) .…”
Section: Hydrolases In Multicomponent and Tandem Nonconventional Reacmentioning
confidence: 99%
“…He et al [74] reported for the first time that hen egg white lysozyme (HEWL) efficiently promotes the onepot, three-component aza-Diels-Alder reaction of aromatic aldehydes, aromatic amine and 2-cyclohexen-1-one. Under optimised conditions, yields up to 98% and stereoselectivity of endo/exo ratios up to 90:10 were obtained.…”
Section: Catalytic Promiscuity: Beyond Lipasesmentioning
confidence: 99%